Effect of plasma treatment on the bond of soft denture liner to conventional and high impact acrylic denture materials - Qanber , Lubna M; Hamad , Thekra I (Journal of Baghdad College of Dentistry, 2021)
Background: The main drawback of soft lining materials was that they debonded from the denture base after a certain period of usage. Therefore, the purpose of this research was to determine the impact of oxygen and argon plasma treatment on the shear bonding strength of soft liners to two different kinds of denture base materials: conventional acrylic resin and high impact acrylic resin. Materials and Methods: Heat cure conventional and high impact acrylic blocks (40 for each group) were prepared. A soft liner connected the final test specimen of two blocks of each acrylic material. Shear bond strength (SBS) was assessed using universal testing machine. Additional blocks were also prepared for analyzing Vickers microhardness, contact angle, FTIR and AFM. The results were statistically analyzed using paired-sample T-test and independent-samples T-test (Î±=0.05). Results: The results showed a highly significant increase in SBS following plasma treatment with the highest mean value observed in plasma treated high impact acrylic specimen. Along with a significant rise in wettability, while microhardness was preserved. Conclusion: In conclusion, oxygen and argon plasma treatment was significantly effective in enhancing the SBS between soft liner and acrylic materials.